2018
DOI: 10.3390/toxins10010024
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Mediated Cell Cycle Arrest and Apoptosis Induced by Zearalenone in Mouse Sertoli Cells via ER Stress and the ATP/AMPK Pathway

Abstract: Zearalenone (ZEA) can perturb the differentiation of cells, reduce the generation of reproductive cells and induce a death of germ cells, but the molecular mechanism remains unclear. In order to investigate the potential mechanism of ZEA-induced cell cycle arrest and apoptosis, we studied the effects of ZEA on cell proliferation, cell-cycle distribution, cell-cycle-related proteins, cell death, cell apoptosis, ROS generation and the ATP/AMPK pathway in Sertoli cells. The role of ROS, ER stress and the ATP/AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 32 publications
8
60
0
Order By: Relevance
“…This observation might be associated with the fact that these two cell lines represent a different models of PCa with a different differentiation ratio and invasiveness of cells. A cell cycle arrest in the G2/M phase associated with ZEA-induced oxidative stress has also been observed by others [22,23]. The MAPK and PI3K/Akt cell signaling pathways are reported to be involved in ZEA-induced effects in cells [24].…”
Section: Discussionsupporting
confidence: 60%
“…This observation might be associated with the fact that these two cell lines represent a different models of PCa with a different differentiation ratio and invasiveness of cells. A cell cycle arrest in the G2/M phase associated with ZEA-induced oxidative stress has also been observed by others [22,23]. The MAPK and PI3K/Akt cell signaling pathways are reported to be involved in ZEA-induced effects in cells [24].…”
Section: Discussionsupporting
confidence: 60%
“…Apart from regulating AJs integrity, SCs proliferation inhibition is also mediated by the AMPK signaling pathway 98 . AMPK activation potentially leads to detention of rat SCs proliferation at least partially by inhibition of mTORC1 and stimulation of cyclin-dependent kinase inhibitors expression.…”
Section: Scs Proliferationmentioning
confidence: 99%
“…Zearalenone (ZEN) is widely distributed mycotoxin, produced by Fusarium species and can exert estrogen-like activity. Zheng et al [71] reported ZEN-induced germ cell death by ROS mediated ER stress in mouse Sertoli cell. Furthermore, ER stress regulates ATP/AMPK pathway, suggest crosstalk between ROS-mediated ER stress and ATP/AMPK pathway and plays key role in ZEN induced cell cycle arrest and cell apoptosis.…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 99%